What Should Constitutions Do? - Paul, Ellen Frankel; Miller, Jr, Fred D.; Paul, Jeffrey (Cambridge : Cambridge University Press, 2011)
The essays in this volume - written by prominent philosophers, political scientists and legal scholars - address the basic purposes of constitutions and their status as fundamental law. Some deal with specific constitutional provisions: they ask, for example, which branches of government should have the authority to conduct foreign policy, or how the judiciary should be organized, or what role a preamble should play in a nation's founding document. Other essays explore questions of constitutional design: they consider the advantages of a federal system of government, or the challenges of designing a constitution for a pluralistic society - or they ask what form of constitution best promotes personal liberty and economic prosperity.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Political science